2007
DOI: 10.1104/pp.107.107441
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose-6-Phosphate Synthase/Phosphatase Regulates Cell Shape and Plant Architecture in Arabidopsis

Abstract: The vacuole occupies most of the volume of plant cells; thus, the tonoplast marker d-tonoplast intrinsic protein-green fluorescent protein delineates cell shape, for example, in epidermis. This permits rapid identification of mutants. Using this strategy, we identified the cell shape phenotype-1 (csp-1) mutant in Arabidopsis thaliana. Beyond an absence of lobes in pavement cells, phenotypes included reduced trichome branching, altered leaf serration and stem branching, and increased stomatal density. This resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 54 publications
3
117
0
Order By: Relevance
“…In this case, EMS mutagenesis and confocal microscopy were used to identify Arabidopsis plants with aberrant distribution of a GFP fusion to a d-tonoplast intrinsic protein. With the same approach, Chary et al (2008) identified a mutant involved in ascribing cell shape and size, dubbed cell shape phenotype-1. Fine mapping identified the gene as a glycosyl-transferase family 20 member, trehalose-6-P synthase/phosphatase.…”
Section: Optical Imaging As a Mutant Screening Toolmentioning
confidence: 99%
“…In this case, EMS mutagenesis and confocal microscopy were used to identify Arabidopsis plants with aberrant distribution of a GFP fusion to a d-tonoplast intrinsic protein. With the same approach, Chary et al (2008) identified a mutant involved in ascribing cell shape and size, dubbed cell shape phenotype-1. Fine mapping identified the gene as a glycosyl-transferase family 20 member, trehalose-6-P synthase/phosphatase.…”
Section: Optical Imaging As a Mutant Screening Toolmentioning
confidence: 99%
“…A TPP from corn, RAMOSA3, for example is expressed in a very restricted cell-file and preliminary results suggest that some TPSs from Arabidopsis have very restricted expression patterns (Satoh-Nagasawa et al, 2006). This contrasts with the expression patterns of AtTPS1 and AtTPS6 that are expressed ubiquitously at all stages of development (Chary et al, 2007;van Dijken et al, 2004). Analysis of the expression of all genes associated with trehalose metabolism in Arabidopsis roots using a dataset generated from cell-sorted root protoplasts is shown in Figure 5 ( Birnbaum et al, 2003;Brady et al, 2007).…”
Section: Expression Of the Genes Associated With Arabidopsis Trehalosmentioning
confidence: 77%
“…AtTPS5 interacts with the transcriptional co-activator MBF1c in vitro in S. cerevisiae two-hybrid assays and is thought to be required for basal thermo-tolerance of Arabidopsis (Suzuki et al, 2008). AtTPS6 was reported to complement S. cerevisiae strains deficient in ScTPS1 growing on glucose and S. cerevisiae strains deficient in ScTPS2 growing at 38 o C (Chary et al, 2007) but this result required further confirmation. Phylogenetic trees constructed with Class II TPS from Arabidopsis, poplar and rice support 5 orthologous groups each including AtTPS5, AtTPS6, AtTPS7, AtTPS8-10 and AtTPS11 (Lunn, 2007).…”
Section: Protein Structures and Possible Functions Of Different Genesmentioning
confidence: 95%
See 2 more Smart Citations